Quantum codes from concatenated algebraic-geometric codes - Chen, Hao (2013)
We apply Steane's enlargement of the Calderbank-Shor-Steane (CSS) codes and additive codes over F4 to concatenated algebraic-geometric codes to construct many good quantum codes with fewer restrictions on the parameters compared to some known quantum codes. Some of the quantum codes we have constructed are either optimal or have parameters as good as the best known codes, while some have parameters better than those obtained from other known constructions.